RESEARCHERSAND EXTENSION WORKERSPERSPECTIVES ON AGRICULTURAL RESEARCH-EXTENSION LINKAGES IN THE KINGDOM OF SAUDI ARABIA - H. S. Kassem; F. O. Aldosari; M. B. Baig; S. Muneer; A. N. Elmajem (Journal of Animal and Plant Sciences, 2018)
There have been multiple mechanisms employed to improve research-extension linkages in the Kingdom of Saudi Arabia. Improving access and adoption of agricultural innovation is the indirect outcome of the research-extension linkages. This study was conducted to describe existing linkages in terms of implementation and strength levels. Moreover, the study identifies factors affecting linkages and explores appropriate approaches to develop and strengthen sustainable research-extension linkages. Data were collected from122 research personnel and 221 extension workers from all regions of the kingdom. Data were generated by administering a structured questionnaire. Percentages, means, standard deviations, the critical ratio (C.R), and t-test were used as statistical tools. The results indicated a significant difference between extension workers and researchers regarding joint technology development and determining farmers needs. It was observed that lack of physical/financial facilities and routine administrative work were among the factors inhibiting extension- research linkages. The study recommends several improvement measures, such as developing the provision of extension services by utilizing ICTs, forming a national coordination committee for planning, and merging research and extension into a single new administration. ability of the research system to transfer agricultural
Keywords: research; agricultural extension; linkages mechanisms; assessment; Saudi Arabia.